Evaluation of Stocking Density during Second‐Year Growth of Largemouth Bass, Micropterus salmoides, Raised Indoors in a Recirculating Aquaculture System. Issue 4 (27th May 2016) - Watts, Chelsea; Bright, Leigh Anne; Coyle, Shawn; Tidwell, James
Abstract: Largemouth bass (LMB), Micropterus salmoides, are a highly desirable food fish especially among Asian populations in large cities throughout North America. The primary production method for food‐size LMB (>500 g) has been outdoor ponds that require two growing seasons (18 mo). Indoor, controlled‐environment production using recirculating aquaculture system (RAS) technologies could potentially reduce the growout period by maintaining ideal temperatures year‐round. Researchers conducted a 26‐wk study to evaluate optimal stocking densities for growout of second‐year LMB to food‐fish size in an indoor RAS. LMB fingerlings (112.0 ± 38.0 g) were randomly stocked into nine 900‐L tanks to achieve densities of 30, 60, or 120 fish/m 3 with three replicate tanks per density. The RAS consisted of a 3000‐L sump, ¼ hp pump, bead filter for solids removal, mixed‐moving‐bed biofilter for nitrification, and a 400‐watt ultraviolet light for sterilization. Fish were fed a commercially available floating diet (45% protein and 16% lipid) once daily to apparent satiation. At harvest, all fish were counted, individually weighed, and measured. Total biomass densities significantly increased ( P ≤ 0.05) with stocking rate achieving 6.2, 13.2, and 22.9 kg/m 3 for fish stocked at 20, 60, and 120 fish/m 3, respectively. The stocking densities evaluated had no significant impact ( P > 0.05) on survival, average harvest weight, or feed conversion ratio which averaged 92.9 ± 5.8%, 294.5 ± 21.1 g, and 1.8 ± 0.3, respectively. After approximately 6 mo of culture, LMB did not attain target weights of >500 g. Observed competition among fish likely resulted in large size variability and overall poor growth compared to second‐year growth in ponds. Additional research is needed to better assess the suitability of LMB for culture in RAS.